2006
DOI: 10.4049/jimmunol.176.10.5749
|View full text |Cite
|
Sign up to set email alerts
|

Redundant Role of Chemokines CCL25/TECK and CCL28/MEC in IgA+ Plasmablast Recruitment to the Intestinal Lamina Propria After Rotavirus Infection

Abstract: Rotaviruses (RV) are the most important cause of severe childhood diarrheal disease. In suckling mice, infection with RV results in an increase in total and virus-specific IgA+ plasmablasts in the small intestinal lamina propria (LP) soon after infection, providing a unique opportunity to study the mechanism of IgA+ cell recruitment into the small intestine. In this study, we show that the increase in total and RV-specific IgA+ plasmablasts in the LP after RV infection can be blocked by the combined administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 43 publications
3
77
0
Order By: Relevance
“…Further detailed analysis of lymphocyte homing in wild-type and CCR9-deficient mice revealed CCR9 expression on IgA 1 plasma cells in mesenteric lymph nodes and Peyer's patches that was downregulated on migration to the small intestine (Pabst et al, 2004). Ccr9 2/2 animals failed to mount a normal IgA response to orally administered antigens (Pabst et al, 2004), although Ccr9 2/2 animals showed no gross defect in rotavirus-specific plasmablast recruitment to the intestine during rotavirus infection (Feng et al, 2006). Given the expression of the CCR9 receptor on guthoming lymphocytes in the blood and lymphocytes in the gut, a number of laboratories looked at the effects of CCR9 ablation and CCL25 blockade in mouse models of intestinal inflammation.…”
Section: Ccr9mentioning
confidence: 99%
“…Further detailed analysis of lymphocyte homing in wild-type and CCR9-deficient mice revealed CCR9 expression on IgA 1 plasma cells in mesenteric lymph nodes and Peyer's patches that was downregulated on migration to the small intestine (Pabst et al, 2004). Ccr9 2/2 animals failed to mount a normal IgA response to orally administered antigens (Pabst et al, 2004), although Ccr9 2/2 animals showed no gross defect in rotavirus-specific plasmablast recruitment to the intestine during rotavirus infection (Feng et al, 2006). Given the expression of the CCR9 receptor on guthoming lymphocytes in the blood and lymphocytes in the gut, a number of laboratories looked at the effects of CCR9 ablation and CCL25 blockade in mouse models of intestinal inflammation.…”
Section: Ccr9mentioning
confidence: 99%
“…The integrin α4β7 allows lymphocytes to specifically attach to the mucosal addressin, cell adhesion molecule-1 (MADCAM-1) [74,80] expressed on endothelial cells of the post capillary venules in the gut lamina propria (LP) thus guiding lymphocytes toward these key gut effector sites [66]. The chemokine receptors CCR9 and CCR10 allow lymphocyte homing to the small or large intestine where endothelial cells produce CCL25 and CCL28 respectively, adding further gut homing specificity [81,82]. Effector responses can consequently be manifested in the LP or between epithelial cells in the case of intra-epithelial lymphocytes (IELs) [83][84][85].…”
Section: Gut Immune Responsesmentioning
confidence: 99%
“…As a result, antibodysecreting cells in the lamina propria express ␣ 4 ␤ 7 integrin. 3,29 Further, CCR10 expression by IgA ϩ plasmablasts mediates their migration toward CCL28, 20,30 which is expressed in gut-and airway-associated lymphoid tissues. 31 Consistently, CCR10 is abundantly expressed by IgA-secreting cells residing within human mucosal effector sites.…”
Section: Rituximab-resistant Mucosal Plasmablasts 5187mentioning
confidence: 99%